Analysis of Islamic Education Learning Innovation Based on Media and Active Methods at IPE Pekanbaru - Rofiatus Sa'adah; Wasith Achadi (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2026)
Islamic Religious Education (PAI) plays an important role in building students’ character and strengthening their religious understanding. However, PAI learning practices are still often dominated by conventional approaches that do not sufficiently involve students’ active participation, which affects their learning interest and understanding. This study aims to analyze media-based and active-method-based PAI learning innovation at Ingenium Primary Education (IPE) Pekanbaru, with a focus on the forms of innovation, the implementation process, and its impact on students. This study used a qualitative approach with a field research design. Data were collected through observation, in-depth interviews with the PAI teacher and the vice principal for curriculum affairs, and documentation. The data were analyzed using an interactive analysis model through data reduction, data display, and conclusion drawing. Data validity was tested through source and technique triangulation. The findings show that PAI learning innovation at IPE Pekanbaru is implemented through the integration of learning media, educational games, and active learning methods, such as problem-based learning, project-based learning, and discovery learning. These innovations are supported by learning technology and religious habituation activities, such as murajaah and congregational prayer. The implementation process is carried out through continuous curriculum evaluation and collaborative planning through Lesson Plan Activity (LPA). The findings indicate an increase in students’ activeness, motivation, and understanding, as well as the strengthening of religious character and the improvement of teachers’ creativity and professionalism. Therefore, the integration of learning media and active methods has the potential to become a relevant strategy for improving the quality of PAI learning in primary schools. Keywords: Islamic Religious Education; Learning Innovation; Learning Media; Active Learning Methods